Snow mountain passage a novel - Houston, James D (new york, 2001)
A proud and devoted husband and father, Reed and his family travel in the palace car, an enormous and ultimately cumbersome covered wagon, thrilling to new sights and coping with conflict and constant danger. yet after a fatal struggle with another driver, Reed is exiled from the party and heads alone over the sierra nevada the final mountain pass. weeks later, the remaining families arrive at the footshills only to be trapped in the imprisoning snows. slowly starving and freezing, for months they battle to survive while Reed journeys across northen california, trying to find means and men for a rescue party. an extraordinary tale of pride and redemption
American corner
11
Keywords: Donnar party -- fiction; English fiction; Overland journey to the pacific -- fiction; Wilderness survival -- fiction; California -- history -- fiction